Monitoring of toxicity of As(V) solutions by AMPHITOX test without and with treatment with zerovalent iron nanoparticles - Perez Coll, Cristina Silvia; Pabón Reyes, Deisy Carolina; Meichtry, Jorge Martin; Litter, Marta Irene (Elsevier Science, 2018)
Fil: Perez Coll, Cristina Silvia. Universidad Nacional de San Martín. Instituto de Investigación en Ingeniería Ambiental; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina